MITOLOGI BUDAYA PADA GELANG DUKACITA SEBAGAI ATRIBUT UPACARA KEMATIAN DALAM TRADISI TIONGHOA BANGKA DAN CINA BENTENG (Tinjauan Semiologi Barthes terhadap Makna Tanda pada Tradisi dan Mitos Leluhur Peranakan Tionghoa Indonesia) - Rustono Farady Marta; Herlika Fransisca Wijaya (Universitas Bunda Mulia, 2015)
The implementation of funeral ceremony has uniqueness, sanctity, and moral values contained in them in the form ceremony as a tradition as well as arts and myths that implied in it. Similarly, in the tradition of funeral ceremony among Peranakan Tionghoa Bangka (Chinese descendants of Bangka Province) and Cina Benteng (Chinese people living in Tangerang, Banten Province) of Indonesia. One of the arts and the myths is exemplified by a bracelet worn by Tionghoa Bangka and Cina Benteng community during the mourning. Even come from two different classes of Chinese society, both have the same view of the significance of the bracelet. This suggests there is a common thread between Tionghoa Bangka and Cina Benteng. The purpose of this study is to determine the meaning contained in the traditions and myths attached to the bracelet as one of the attributes of the death ceremony of Tionghoa bangka and Cina Benteng. This research uses theory of semiotics as formulated by Roland Barthes. This study used qualitative research method with descriptive analysis. The methodology used is semiotics. All data was collected by connecting the visible sign of the mourning bracelet as one of the attributes of the funeral ceremony, combined with literature studies. The research object consists of attributes which are used by Those who are Bangka Chinese and Cina Benteng, then the implied meanings are explored in depth and correlated with the arts in the ceremony tradition as well as the myths which developed as an Indonesian-Chinese’s heritage. Keywords: Mourning Bracelet, Tradition and Myth, Semiotic Studies